Chanter la diversité culturelle en Occitanie : Ethnographie performative d’une tradition réimaginée - Magnat, Virginie (Anthropologica, 2018)
This performative ethnography of Occitan cultural resurgence through the practice of traditional song and music is situated at the intersection of anthropology, ethnomusicology, sociology, and the interdisciplinary field of performance studies. Based on her fieldwork in Occitania as an artist-scholar, the author proposes a critical and reflexive approach that combines the imaginary with historicity and the legendary with the performative to question the future of an intercultural musical tradition which she associates with her Mediterranean roots. Aiming to produce what D. Soyini Madison (2012) calls a performance of possibilities, the author lets us see/read/imagine an Occitania revitalized by diversity, inclusion, and solidarity, thereby offering an alternative to nationalist constructions of cultural identity rooted in France’s colonialist legacy and to the disturbing resurgence of far-right movements in Europe.